Stadtpalais und Belvedere des Prinzen Eugen Entstehung, Gestalt, Funktion und Bedeutung - Seeger, Ulrike (2004)
Prince Eugene of Savoy, contemporary and companion in arms of the first Duke of Marlborough, was the architectural patron of two of the most important buildings of the Viennese baroque, viz. the Stadtpalais (city mansion) and the Belvedere, a suburban garden palace. In spite of the common patron, so far the two buildings were considered quite separately by the research on the Viennese baroque, presumably because of the emphasis on the two different, very prominent architects, Johann Bernhard Fischer von Erlach and Johann Lucas von Hildebrandt. In the unified view presented in the present work, attention is focussed not only on the architecture but also on the sequences of rooms, on their interior decoration, and - in the case of the Belvedere - on the conceptual relationship between garden and buildings. Starting point is the question: "What was the self-representation intended by the Prince, who had not been raised in the Habsburg monarchy but at the French court?" The investigation of the origins of the various elements of the interior decoration and of the messages going with their provenance was helped by the fortunate circumstance that not only are the buildings well preserved but that, through the contemporary engravings and drawings of Salomon Kleiner, we are well informed on the original interiors of the buildings. Together with newly discovered written sources, this has allowed the complicated plannings, construction and decoration history of the two palaces to be clarified. The main results may be summarized as follows. Prince Eugene of Savoy wished to conform, on a high level, to the traditions and the style of the Viennese nobility but without foregoing the French achievements in living comfort and elegance he was acquainted with from his time at the French court. As his carrier progressed, this 'French component' was enhanced and made increasingly visible. Little prominence was given to the relationship of the Prince to the ruling house of Savoy, presumably because he wanted to leave no doubt that he owed his position as one of the leading military and political leaders of the time not to family connections but to his own achievements.